Spatial variability and changes in carbon stocks of a Regosols (Psamments) cultivated with sisal - José A. A. S. do Sacramento; Jorge A. G. Santos; Diego C. Loureiro; Oldair V. Costa; Alide M. W. Cova (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Information on spatial variability and soil carbon stocks after the conversion of Caatinga vegetation to different cropping systems is scarce. This study aimed to characterize the spatial variability and to evaluate the changes in carbon stocks and the emission of greenhouse gases after the conversion of Caatinga vegetation with different sisal cultivation systems. The study was carried out in three areas in the city of Valente, Bahia, two areas that had been cultivated for 20 years with sisal in either a traditional (TSC) or alternative (ASC) system, and the third area containing natural Caatinga vegetation. The cultivated soils were sampled at 40 soil sampling points with 15 × 10 m spacing at depths of 0-0.20 and 0.20-0.40 m. Total organic carbon (TOC) stocks had spatial dependence and the isoline maps allowed the variability in the studied depths to be analyzed. The conversion of Caatinga vegetation to sisal cultivation using traditional farming systems caused a 30% decrease in soil TOC stocks. Moreover, the alternative culture system caused an 11% increase in soil TOC stocks. The emission factor or carbon absorption due to changes in land use after 20 years was 0.66 t ha-1 yr-1 of carbon in the traditional farming system and -0.25 t ha-1 yr-1 of carbon in the alternative culture system.